The use of processed polyethylene products in the manufacture of plastic lubricants - Grigorov, Andrey; Zelenskii, Oleg (My University, 2019)
It is proposed to expand the raw material base for the production of greases by using used motor oils and solid waste polyethylene products. The results of a laboratory study have been presented; they made it possible to establish that the optimal concentration of the thickener in oil fluctuates within a rather narrow range of 5.0–7.0 wt%. Thus, the obtained greases are identical in quality to the greases of the type Estan 2 (Exxon Co.) and AGIP Grease CC 2 but are much cheaper in produc-tion. The approach to attracting secondary energy resources to the technological process of greases production will meet the existing demand for lubricants and significantly reduce the envi-ronmental burden on the environment.
Keywords: secondary hydrocarbon raw materials; plastic grease; thickener; base oil; polyethylene products; quality indicators; adhesive ability